Comparison of different exercise modalities in women with polyendocrine metabolic ovarian syndrome: a narrative review - Szarek, Bogumiła; Szarek, Rafał (Quality in Sport, 2026)
Polyendocrine metabolic ovarian syndrome (PMOS), formerly known as polycystic ovary syndrome (PCOS), is a complex endocrine and metabolic disorder associated with insulin resistance, chronic low-grade inflammation, reproductive dysfunction, and reduced quality of life. Although physical activity is a cornerstone of PMOS management, the relative effectiveness of different exercise modalities remains unclear. To compare the effects of aerobic exercise, resistance training, and high-intensity interval training (HIIT) on metabolic, reproductive, inflammatory, and psychological outcomes in women with PMOS. A narrative literature review was conducted using PubMed and Google Scholar. Original studies, randomized controlled trials, observational studies, reviews, and clinical guidelines evaluating exercise interventions in women with PMOS/PCOS were included. Due to heterogeneity in study designs and outcomes, findings were synthesized qualitatively. Aerobic exercise, resistance training, and HIIT all demonstrated beneficial effects in women with PMOS. Aerobic exercise improved body composition, insulin sensitivity, cardiovascular fitness, and psychological well-being. Resistance training was particularly effective in increasing lean body mass and improving metabolic health, whereas HIIT provided a time-efficient strategy with favorable effects on insulin sensitivity and cardiorespiratory fitness. Combined exercise interventions appeared to offer the broadest benefits by targeting multiple pathophysiological mechanisms. Exercise is a key component of PMOS management. Although no single modality appears universally superior, resistance training and HIIT may provide additional metabolic benefits beyond aerobic exercise. Exercise programs should be individualized according to patient characteristics and treatment goals. Further high-quality randomized controlled trials are needed to establish evidence-based recommendations for optimal exercise strategies in women with PMOS.